2018
DOI: 10.1159/000489741
|View full text |Cite
|
Sign up to set email alerts
|

SCCA, TSGF, and the Long Non-Coding RNA AC007271.3 are Effective Biomarkers for Diagnosing Oral Squamous Cell Carcinoma

Abstract: Background/Aims: Oral squamous cell carcinoma (OSCC) is one of the most lethal malignancies worldwide and the most common type of oral cancer, characterized by invasive growth, frequent regional metastases, high recurrence, and poor prognosis. In the current study, we investigated the use of long non-coding RNAs (lncRNAs), tumor-specific growth factor (TSGF), and squamous cell carcinoma antigen (SCCA) as potential biomarkers for OSCC screening. Methods: LncRNA expression was measured by microarray analysis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Although it is easily detected, up to 60% of OSCC cases are undiagnosed in early clinical stages. The biomarkers 4 for early diagnosis of OSCC are therefore crucial to improving patient prognosis and survival rates.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is easily detected, up to 60% of OSCC cases are undiagnosed in early clinical stages. The biomarkers 4 for early diagnosis of OSCC are therefore crucial to improving patient prognosis and survival rates.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicated that lncRNA is closely related to tumorigenesis and development. Our recent studies con rmed that aberrant AC007271.3 levels in OSCC patients were signi cantly associated with clinical stage, especially in early-stage disease and serum AC007271.3 levels could also discriminate between OSCC and normal controls with high sensitivity and speci city, which suggesting that AC007271.3 could be a novel circulating biomarker for the determination of OSCC [11] . Furthermore, we found that AC007271.3 could promote cell proliferation, invasion and inhibit cell apoptosis of OSCC via the Wnt/β-catenin signaling pathway, which might provide a novel therapeutic approach for OSCC [12] .…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, the lncRNAs KCNQ1OT1 and SNHG17 act as competing endogenous RNAs (ceRNAs) to control cell proliferation and cancer progression in TSCC [3,8] . In addition, recent studies revealed that lncRNA combined with mRNA biomarkers could improve diagnosis [9] [10] . However, there are limited valuable lncRNA and mRNA biomarkers used for the diagnosis of TSCC.…”
Section: Introductionmentioning
confidence: 99%